Reliability and validity of the international physical activity questionnaire short-form (IPAQ-sf) in COPD - Flora, Sofia (2022)
Physical activity (PA) may improve COPD prognosis, thus its assessment and promotion are crucial. The International Physical Activity Questionnaire Short-Form (IPAQ-sf) is widely used for assessing PA but there is limited evidence on its clinimetric properties in COPD. We assessed the test-retest reliability and validity of the IPAQ-sf in patients with COPD. Fifty-five participants (68.6±7.8yrs, 48 males, FEV1 52.3±22.5%pred) completed the IPAQ-sf, wore an accelerometer for 7 days and completed a second IPAQ-sf. Test-retest reliability/agreement was assessed with: Intraclass Correlation (ICC, 95%CI), 95% Limits of Agreement (LoA), standard error of measurement (SEM) and minimal detectable change (MDC95) for continuous variables; %agreement for categories (“active” vs “inactive”). Validity was assessed with Spearman’s correlations (ρ) between the IPAQ-sf (METs-min/week, time in vigorous [VPA] and moderate PA [MPA] per week) and accelerometry [time in MVPA, VPA and MPA per week] for continuous variables; %agreement, Cohen’s kappa, sensitivity and specificity (95%CI) for categories. Reliability was acceptable (ICC=0.738, 0.629→0.873) but with wide LoA (-5713→4793.3 METs-min/week). SEM and MDC95 were 1844.7 and 5113.3 METs-min/week, respectively. %agreement of the two IPAQ-sf was 85.5% (kappa=0.660, 0.444→0.876). Significant correlations were found between METsmin/week and accelerometry (0.515≤ρ≤0.596), except for VPA (p>0.05). %agreement between tools was 67.3% (kappa=0.350, 0.279→0.571) with high sensitivity (0.89, 0.887→0.891) but low specificity (0.46, 0.46→0.47). The IPAQ-sf could be used as PA measurement tool in COPD although caution is needed to avoid misclassification.